Development of an e-financial organizer for young adults / Noor Farlina Rosli - Rosli, Noor Farlina (2006)
Money is an essential part of life that cannot be excluded. The importance of money has become stressful to many people of all ages. The moment a person enters the working environment, they have to take responsibility over their own finances. Students who are about to graduate universities are aware of financial problems, but are still reluctant to take action about their future. There are many financial strategies out there just waiting for us to grab them. By creating a free online application about money management, there may be a chance to attract these youngsters to start appreciating their money. Using a rule based expert system, it is possible to construct an e-financial organizer that can act as a user's personal financial diary. It may assist the user in financial decision making, thus disciplining the user whilst unconsciously bringing up the appreciation for money. This project focuses on the development of an e-Financial Organizer for Young Adults based on the survey done on the need for this application. The commercialization of this application may increase the interest of students and young adults to start educating themselves deeply in the knowledge of personal finance management